Analysis of global trends in acute lymphoblastic leukemia in children aged 0–5 years from 1990 to 2021 - Ding, Fang; Deng, Lili; Xiong, Jingxuan; Cheng, Zugen; Xu, Jiaoli (Frontiers in Pediatrics, 2025)
BackgroundAcute lymphoblastic leukemia (ALL) is the most common pediatric cancer, with a significant global burden. This study evaluates global, regional, and national trends in the prevalence, mortality, and disability-adjusted life years (DALYs) of childhood ALL from 1990 to 2021, providing insights into disparities and progress across different socio-demographic and geographic contexts.MethodsData were sourced from the Global Burden of Disease study. Trends in prevalence, mortality, and DALYs were analyzed by socio-demographic index (SDI) regions, geographic areas, and countries. Estimated annual percentage changes (EAPCs) were used to quantify temporal trends.FindingsBetween 1990 and 2021, the global number of childhood ALL cases increased by 59.06%, reaching 168,879 cases in 2021, while ALL-related deaths and DALYs decreased by 66.71% and 66.13%, respectively. High- and high-middle SDI regions demonstrated significant improvements, driven by advances in healthcare and early diagnosis. In contrast, low-SDI regions faced persistent challenges, with a slight increase in DALYs observed in 2021. Geographic disparities were pronounced, with East Asia achieving the largest reductions in mortality and DALYs, whereas Sub-Saharan Africa and the Caribbean remained heavily burdened.InterpretationDespite progress in reducing mortality and DALYs globally, the rising prevalence of ALL and persistent disparities in low-SDI regions highlight the urgent need for equitable access to healthcare, early diagnosis, and effective treatment strategies. Strengthening healthcare infrastructure and fostering global collaboration are critical to further mitigating the burden of childhood ALL and ensuring equitable outcomes worldwide.